Determinan Return Saham dengan Analisis Profitabilitas dan Sustainability Report - Rahayu, Sri (JURNAL EKONOMIKA, 2024)
Stock returns are one of the important factors that investors pay attention to before investing. One sector that investors are interested in is the banking sector because this sector produces a large profit. Before investing, investors usually need information contained in financial reports and non-financial reports to calculate the stock return that investors will get in the future. This study aims to determine The Effect of Profitability and Sustainability Report on Stock Return. The sample selection technique in this study used a purposive sampling method and obtained 11 banking sub-sector companies listed on the Indonesia Stock Exchange for the 2018-2022 period. The data analysis method used in this study is multiple linear regression analysis using the SPSS program version 22. Based on the results of this study, it can be concluded that profitability and sustainability report on environmental performance have a positive and significant effect on stock return, while sustainability report on economic performance and sustainability report on social performance have no effect on stock return.